2016
DOI: 10.4103/1947-2714.183013
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of her2, ki67, and p53 in osteosarcoma: A strong prognostic factor

Abstract: Background:Many laboratories are currently evaluating the usefulness of the determination of human epidermal growth factor receptor 2 (HER2), p53, and Ki67 proliferation indices using immunohistochemical techniques in cancer. Although the available studies suggest that these factors might indeed be helpful in making treatment decisions in osteosarcoma patients, their clinical usefulness is still controversial.Aims:We proposed to introduce the value of the coexistence of HER2 overexpression, p53 protein accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 16 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…9 Ki67 has been reported to be significantly upregulated in a variety of tumor tissues and cells, such as lung, 10 gastric, 11 colon, 12 ovarian, 13 and OS. 14 Our results are consistent with these reports. Ki67 expression was significantly suppressed by SRPX2 knockdown.…”
Section: Dovepresssupporting
confidence: 94%
“…9 Ki67 has been reported to be significantly upregulated in a variety of tumor tissues and cells, such as lung, 10 gastric, 11 colon, 12 ovarian, 13 and OS. 14 Our results are consistent with these reports. Ki67 expression was significantly suppressed by SRPX2 knockdown.…”
Section: Dovepresssupporting
confidence: 94%
“…The tumor volume and weight were smaller in the MCM2 and MCM3 knockdown groups than the scramble group (Figure 4B–4D). As shown in Figure 4E and 4F, based on an immunohistochemical analysis, the levels of the tissue proliferation marker Ki-67 [18] was lower in the sh-MCM2 and sh-MCM3 tumors compared to those in sh-control tumors. Taken together, these results indicated that MCM2 or MCM3 knockdown could hinder the tumorigenesis of osteosarcoma cells in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Over-expression of MTA-1 has been noted in high-grade osteosarcoma tumor samples with little to no expression in low-grade samples (9). Mardanpour et al evaluated tumor samples from 56 osteosarcoma patients and noted a correlation between increased p53 and Ki67 with worse PFS and OS (18). In 47 resected osteosarcomas following neoadjuvant chemotherapy, increased p53 expression correlated with worse overall survival while expression in biopsy samples was not predictive of chemotherapy response or survival (19).…”
Section: Discussionmentioning
confidence: 99%